The Role of Human Resource Planning on the Improvement of Employees’ Recruitment Process - Khalilurahman Sarwary; Faizulhaq Faizi; Mohammad Rafee Banayee (HM Journals, 2022)
Human resource planning (HRP) is one of the most important human resource tasks in the organization. Organizations relies much on human resource planning to determine their current and future needs of manpower. HRP is a vital process in an organization as it gives indication on areas of need. Human resource planning is a process of forecasting the organization’s demand and supply of manpower needs in the present and future. Recruitment involves finding and attracting right and qualified candidates to fill the position in the organization structure. The purpose of this article is to investigate the role and importance of the HRP to the employees’ recruitment and selection process. This research was a disk study based on information from reliable books, articles and scientific papers. Findings revealed that human resource planning in the organization improves the process of recruiting volunteers and facilitates the selection of a qualified and right person in the right place and at the right time. HRP is the heart of the organization and the recruitment process and is the backbone of the organization. Without human resource planning and effective employment policy, no organization can achieve to success and development. When a position becomes vacant in the organization for any reason, the human resources planning will inform the organization. In addition, HRP improvesperformance, satisfaction, development, evaluation and appropriate maintenance and protection of human resources in the organization.